Protocol for measuring the benefits of exergames on executive functions under depression through a randomized multi-arm controlled experiment - Eloisa Ruiz-Marquez (Exploration of Neuroscience, 2024)
Depression is characterized by affective symptoms and neuropsychological deficits. After treatment, affective symptoms frequently remit, but cognitive alterations may remain affecting the lives of people and having an impact on health, economy, and societies. The present work describes the methods, procedures, and equipment for a randomized three-arm controlled experiment designed to measure the effects of exergames on executive functions (EFs) under depression. EFs are complex cognitive functions that are essential for organizing information, planning an action, reasoning, decision-making, and problem-solving. Literature shows that EFs are compromised in depression, affecting daily-life activities and other cognitive domains. To conduct the experiment, depressed middle-aged adults will be randomly distributed into three experimental groups: an intervention group training with exergames, an active control group training only with cognitive video games, and a passive control group or wait-list. EFs are evaluated at three different time points: pre-post intervention, and three months follow-up, using the Wisconsin Card Sorting Test (WCST). Researchers will collect cognitive-behavioral and neural information [event-related potentials (ERPs)]. Results will be explored by performing analysis of variance to compare the outcomes of the diverse groups at the three different time points, understanding the benefits of exergames in terms of EFs under depression. The study of simultaneous multidomain interventions in depression holds promise for the development of novel approaches, to implementing psychological and neuropsychological health [this experiment is part of a registered clinical trial entitled “MUDgame” (ClinicalTrials.gov identifier NCT06536530). Registered on August 2024, https://clinicaltrials.gov/study/NCT06536530].